Preference dynamics: A procedurally rational model of time and effort allocation - Markus Krecik (Freie Universität Berlin, School of Business & Economics, 2024)
Current time allocation and household production models face three major weaknesses: First, they only describe the average time allocation. Thus, information about the order of activities is lost. Therefore, it is impossible to describe the influence of activities on later ones. Such interactions are likely pervasive, and can significantly alter behavior. Second, they are unable to describe the effort allocation of individuals, although effort influences one's time allocation. Thereby, they are either unable or very limited in describing labor productivity or multitasking although individuals frequently multitask. Through the omission of interactions and effort allocation, current models yield biased descriptions of e.g. price and time elasticities. Third, they require strong assumptions, such as perfect foresight or periodic environments, and thus cannot describe behavior in unpredictable environments, like reactions to external shocks. In this paper, I provide a remedy for these shortcomings by developing a dynamical model of procedurally rational decision making. The basic idea of the model is a feedback loop between experienced utility, decision utility, and activities. In applications of the model, I show how introducing a work-leisure interaction and multitasking significantly changes elasticities and how nonmarginal external shocks cause short-term demand surges, none of which can be described by current time allocation models.
urn:nbn:de:kobv:188-refubium-42523-6
Keywords: C61; C63; D11; D90; J22; 330; Preferences; Decision-Making; Behavioral Economics; Procedural Rationality; Household Economics